Tradução e adaptação cultural do WORC: um questionário de qualidade de vida para alterações do manguito rotador - Lopes, Ad [UNIFESP] (2006)
OBJECTIVE: To accomplish the translation of WORC (The Western Ontario Rotator Cuff Index) into Portuguese and its cultural adaptation, for future validation in Brazil. METHOD: The protocol applied consisted of: 1) Preparation; 2) Forward translation; 3) Back translation; 4) Cognitive Debriefing; and 5) Information report. After concluding the forward and back-translations, the versions were sent to the authors of the original questionnaire, who gave their approval for the study to be continued. The Portuguese version was applied to 35 patients with rotator cuff dysfunctions to verify the level of understanding of the instrument. The mean age of these patients was 57 years (SD = 13); 63% were female and 74% had not completed elementary school. The final Brazilian version of WORC was defined after achieving a no comprehension rate of less than 15% for each item. Descriptive statistics were used to analyze the variables. RESULTS: Some terms and expressions were changed or replaced to obtain cultural equivalence for WORC. The terms that were incomprehensible to the patients were changed in accordance with their own suggestions. CONCLUSION: After the translation and cultural adaptation of the questionnaire, the final Portuguese version of WORC was concluded and it is now undergoing validation for use in Brazil.